Neuraxial block and postoperative epidural analgesia: effects on outcomes in the POISE-2 trial. (January 2016) - Leslie, K.; McIlroy, D.; Kasza, J.; Forbes, A.; Kurz, A.; Khan, J.; Meyhoff, C.S.; Allard, R.; Landoni, G.; Jara, X.; Lurati Buse, G.; Candiotti, K.; et al.
Abstract: Background: We assessed associations between intraoperative neuraxial block and postoperative epidural analgesia, and a composite primary outcome of death or non-fatal myocardial infarction, at 30 days post-randomization in POISE-2 Trial subjects. Methods: 10 010 high-risk noncardiac surgical patients were randomized aspirin or placebo and clonidine or placebo. Neuraxial block was defined as intraoperative spinal anaesthesia, or thoracic or lumbar epidural anaesthesia. Postoperative epidural analgesia was defined as postoperative epidural local anaesthetic and/or opioid administration. We used logistic regression with weighting using estimated propensity scores. Results: Neuraxial block was not associated with the primary outcome [7.5% vs 6.5%; odds ratio (OR), 0.89; 95% CI (confidence interval), 0.73–1.08; P +0.24], death (1.0% vs 1.4%; OR, 0.84; 95% CI, 0.53–1.35; P +0.48), myocardial infarction (6.9% vs 5.5%; OR, 0.91; 95% CI, 0.74–1.12; P +0.36) or stroke (0.3% vs 0.4%; OR, 1.05; 95% CI, 0.44–2.49; P +0.91). Neuraxial block was associated with less clinically important hypotension (39% vs 46%; OR, 0.90; 95% CI, 0.81–1.00; P +0.04). Postoperative epidural analgesia was not associated with the primary outcome (11.8% vs 6.2%; OR, 1.48; 95% CI, 0.89–2.48; P +0.13), death (1.3% vs 0.8%; OR, 0.84; 95% CI, 0.35–1.99; P +0.68], myocardial infarction (11.0% vs 5.7%; OR, 1.53; 95% CI, 0.90–2.61; P +0.11], stroke (0.4% vs 0.4%; OR, 0.65; 95% CI, 0.18–2.32; P +0.50] or clinically important hypotension (63% vs 36%; OR, 1.40; 95% CI, 0.95–2.09; P +0.09). Conclusions: Neuraxial block and postoperative epidural analgesia were not associated with adverse cardiovascular outcomes among POISE-2 subjects.